5m-2m+9=-12

Simple and best practice solution for 5m-2m+9=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m-2m+9=-12 equation:


Simplifying
5m + -2m + 9 = -12

Reorder the terms:
9 + 5m + -2m = -12

Combine like terms: 5m + -2m = 3m
9 + 3m = -12

Solving
9 + 3m = -12

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 3m = -12 + -9

Combine like terms: 9 + -9 = 0
0 + 3m = -12 + -9
3m = -12 + -9

Combine like terms: -12 + -9 = -21
3m = -21

Divide each side by '3'.
m = -7

Simplifying
m = -7

See similar equations:

| z^2=-3z+2 | | x^2=-12x+6 | | X+666x=0 | | 127=(2x+41) | | 7z^2+8z-5=0 | | 8x-8-6x=20 | | x=x+32 | | 6(x+5)-6=48-2x | | 5y+8=-1 | | 6(x+5)-6=48 | | 5(x-9)=7(x-3) | | 7y^2-8y-7=0 | | 3(X+2)(2x-10)=0 | | 8x^2=26x+357 | | .81t^2+140=0 | | 4+(-3)2= | | (x+5)=(3x-1) | | -0.3-2.7=-4.1 | | B+8=2 | | 5(r+3)=4+2r+2 | | x-2.3=6.4 | | 750=y+(y*.07) | | 15-3x=7x+5 | | 6cos-1=2 | | 4(q)=52 | | 2(4x+1)=3x-9x | | 1996.43x=7385-67x | | R-(-5)=9 | | 8(4-n)+2=90 | | 44221=a*2+b | | 2(5x+7)+3=10x+17 | | 2x-17=2x-12 |

Equations solver categories